How chinese learners of L2 European Portuguese interpret null and overt pronouns in forward and backward anaphora - Zheng, Yi (2019)
In a questionnaire study we investigate how native speakers of European Portuguese (EP) and Chinese, as well as Chinese learners of EP as second language (L2), interpret null and overt pronouns in forward and backward anaphora. Results show that EP native speakers exhibit different interpretative biases for null and overt pronominal subjects in both forward and backward anaphora. Chinese native speakers show similar interpretation in backward anaphora in their L1 but a subject preference with both null and overt pronouns in forward anaphora conditions. Chinese learners of L2 EP present an overall preference to interpret both pronouns as referring to the subject referent, although there is a developmental effect towards the target interpretation in overt pronoun backward anaphora conditions. Results confirm previous studies in L2 EP (Madeira et al., 2012; Lobo et al., 2017), but add the possibility that this pattern may be explained by L1 influence.